Protective Actions of PPAR-γ Activation in Renal Endothelium. (26th February 2009) - Westerweel, Peter E.; Verhaar, Marianne C.
Abstract : Renal endothelial damage is pivotal in the initiation and progression of renal disease. Damaged renal endothelium may be regenerated through proliferation of local endothelium and circulation-derived endothelial progenitor cells. Activation of the PPAR-γ -receptors present on endothelial cells affects their cellular behavior. Proliferation, apoptosis, migration, and angiogenesis by endothelial cells are modulated, but may involve both stimulation and inhibition depending on the specific circumstances. PPAR-γ -receptor activation stimulates the production of nitric oxide, C-type natriuretic peptide, and superoxide dismutase, while endothelin-1 production is inhibited. Together, they augment endothelial function, resulting in blood pressure lowering and direct renoprotective effects. The presentation of adhesion molecules and release of cytokines recruiting inflammatory cells are inhibited by PPAR-γ -agonism. Finally, PPAR-γ -receptors are also found on endothelial progenitor cells and PPAR-γ -agonists stimulate progenitor-mediated endothelial repair. Together, the stimulatory effects of PPAR-γ -agonism on endothelium make an important contribution to the beneficial actions of PPAR-γ -agonists on renal disease.